LANDSAT and its application to evaluate the dynamics of the health condition of birch stands - E. Kula; M. Stoklasa (Journal of Forest Science, 2003)
Methods were elaborated that would specify factors affecting the accuracy of the output of LANDSAT satellite images used to evaluate the dynamics of changes in the health condition of birch stands. In the period of investigations, in 1994-2000, the foliage of birch stands was very thin as a consequence of the large-scale absence of flushing in 1997. The output of this method is also specification of the degree of foliage of birch trees based on the altitude, stand age and forest site types in the air-polluted area of the Krušné hory Mts. (Northern Bohemia). These methods can be applied to other broadleaved stands.